Knowledge Level of Elderly with Diabetes Mellitus, Hypertension Against Covid-19 Vaccine in Panti Griya Jannati, Gorontalo City - Haslinda Damansyah; Andi Nuraina Sudirman; Abdurahman Nur Kamiden; Miftahul Jannah; Putri Indrawati Nusi (Journal of Universal Community Empowerment Provision, 2021)
Elderly people are people whose biological systems undergo structural and functional changes due to advanced age. These changes can take place smoothly so that they do not cause disability or can occur very real and result in total disability. Hypertension is a silent killer where symptoms can vary in each individual and are almost the same as the symptoms of other diseases. Diabetes mellitus (DM) is a disorder of carbohydrate, lipid, and protein metabolism with various causes and is a chronic disease. A person with diabetes has high blood glucose levels, also known as hyperglycemia. The purpose of this community service is so that the elderly can increase their knowledge about hypertension and diabetes mellitus against the covid-19 vaccine. From the results achieved with this activity, the orphanage is very supportive and gives thanks to the Muhammadiyah University of Gorontalo in conducting outreach education in the form of leaflets and banners. The conclusion of this community service is that counseling can increase knowledge about hypertension and diabetes mellitus against the covid-19 vaccine